Estudo sobre a ação do íon haleto na síntese de resinas epóxi líquidas e na hidrólise do óxido de propileno - Carvalho, Marcus Vinicius dos Santos (Universidade Federal de São Carlos, 2016)
“A STUDY ON THE ROLE OF HALIDE ION IN THE SYNTHESIS OF LIQUID EPOXY RESINS AND ON THE HYDROLISIS OF PROPYLENE OXIDE” is on two aspects of the halide ion in chemistries of liquid epoxy resin and the propylene oxide in the industrial context. The first theme is the improvement of quantification methodology of the residual halide content in the finished resin. To understand the occlusion process of the halide ion, the reactions of the resin syntheses and the molecular aspects are reviewed. The analytical procedure in use is compared with a modified methodology proposed for the determination of residual halide content. The second theme is the equilibrium in the propylene oxide preparative reaction in saline solution and the application of the study results into the improvement of propylene oxide scrubbing process from the purge vapors arising along the handling chain.
A study on the role of halide ion in the synthesis of liquid epoxy resins and on the hydrolisis of propylene oxide
Keywords: Haleto residual; Resina epóxi líquida; Óxido de propileno; CIENCIAS EXATAS E DA TERRA::QUIMICA